2022
DOI: 10.3390/microorganisms10051020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Changes in the Gut Microbiota of Healthy Mice Fed with Lactic Acid Bacteria and Bifidobacteria

Abstract: Probiotics are living microorganisms that provide numerous health benefits for their host. Probiotics have various effects on the body; for example, they change gut microbiota, improve the integrity of the epithelial barrier and have anti-inflammatory effects. The use of probiotic supplements that are based on lactic acid bacteria and bifidobacteria is one of the approaches that are used to balance gut microflora. In our study, we evaluated the effects of supplements, which were based on members of the Lactoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 66 publications
3
21
0
Order By: Relevance
“…In addition, there were seven species of bacteria with a significant difference at the family level, according to the LDA effect size analysis. Lactobacillaceae can protect the gut by inhibiting pathogen colonization ( 68 , 69 ) and have a positive effect on the feed efficiency of chickens ( 70 ). Bifidobacteriaceae have shown beneficial effects in an animal, such as promoting nutrient absorption and improving immunity ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were seven species of bacteria with a significant difference at the family level, according to the LDA effect size analysis. Lactobacillaceae can protect the gut by inhibiting pathogen colonization ( 68 , 69 ) and have a positive effect on the feed efficiency of chickens ( 70 ). Bifidobacteriaceae have shown beneficial effects in an animal, such as promoting nutrient absorption and improving immunity ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia was confirmed to be positively associated with MET treatment for diabetes and with the expression of tight junction proteins and the integrity of the intestinal barrier (Gryaznova et al. 2022 ). Interestingly, Verrucomicrobia and Akkermansia were individually enriched in the SZP group, suggesting that SZP treatment enhanced intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of pathogenic bacteria Bilophila , Tyzzerella , Bryobacter , Comamonas , and Candidatus_Solibacter was significantly downregulated in the MOS group [ 68 , 69 , 70 ]. Tyzzerella was strongly positively associated with the risk of high cardiovascular risk and obesity-related diseases [ 71 , 72 ]. In this study, Tyzzerella was found to present a strong positive correlation with pro-inflammatory factors, which was in agreement with the findings of Grant et al [ 73 ].…”
Section: Discussionmentioning
confidence: 99%